Cape Valmarinniemi: The Cemetery of Medieval Kemi Parish in Northern Finland. - Ikäheimo, Janne; Maijanen, Heli; Matila, Tuuli; Pelttari, Paula (Medieval Archaeology, 2020)
CHRISTIANISATION IS A PROCESS that manifests as locally distinctive traditions and behaviours. While traditionally in Finland it has been assumed that local populations were subjected to a forced conversion, recent research has abandoned such top-down approaches and has emphasised local agency in the Christianisation process. This article contributes to the investigation of religious conversion in the Bothnian Bay coastal region of Finland, where the northernmost Catholic parish of Kemi was established in the early medieval period. The site under scrutiny, the Cape Valmarinniemi burial ground, presents archaeological evidence that questions long-held assumptions about the area's Christianisation. We employ AMS-radiocarbon dating, geographic information systems (GIS) mapping, and a thorough osteological analysis to examine the site. This article addresses the importance of scientific methods and the careful analysis of excavation data in the investigation of religious transformations.